If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(x + -9) + -4(x + 5) = -1 Reorder the terms: 6(-9 + x) + -4(x + 5) = -1 (-9 * 6 + x * 6) + -4(x + 5) = -1 (-54 + 6x) + -4(x + 5) = -1 Reorder the terms: -54 + 6x + -4(5 + x) = -1 -54 + 6x + (5 * -4 + x * -4) = -1 -54 + 6x + (-20 + -4x) = -1 Reorder the terms: -54 + -20 + 6x + -4x = -1 Combine like terms: -54 + -20 = -74 -74 + 6x + -4x = -1 Combine like terms: 6x + -4x = 2x -74 + 2x = -1 Solving -74 + 2x = -1 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '74' to each side of the equation. -74 + 74 + 2x = -1 + 74 Combine like terms: -74 + 74 = 0 0 + 2x = -1 + 74 2x = -1 + 74 Combine like terms: -1 + 74 = 73 2x = 73 Divide each side by '2'. x = 36.5 Simplifying x = 36.5
| 1/2n15 | | y=(-1/2x)2+6x+3 | | (Y+3)(y-12)=0 | | x^2-11x+30=(x-5)(x+6) | | 1/4x+1/8=3/4x-7/8 | | M=2/5(4y+2x) | | 2(3+x)+5=x | | x-5+3x-21+12-3x=4x5 | | x+4+4x+10(x-1)= | | (Y+3)(y-12)= | | x(x+4)=x^2+4 | | 24=g/2-14 | | 5k=0.35 | | y=6x^2+5x+7 | | 3(x-3)+3(x-3)+(x+3)+(x+3)=84 | | 2g=0.6 | | 4x+6x-8=1+7x | | 14f-66=5f+87 | | 2g+97=5g-98 | | 4x(2)=28 | | 8f+50=57f-97 | | 13z+13=23z-67 | | -(5/2)x+(7/3)=-(3/4)x-4 | | 40q+99=72q-93 | | 4b+41=7b-1 | | y=6x^2+7x+10 | | 4y+29=6y-71 | | 14j+68=56j-100 | | (6x^2+15x+4)/(x+2) | | 26x+16=51x-34 | | 8b+49=13b-91 | | 4y+3/5=3/4 |